Rational Design of pH‐Responsive DNA Motifs with General Sequence Compatibility. Issue 46 (1st October 2019) - Fu, Wenhao; Tang, Linlin; Wei, Gaohui; Fang, Liang; Zeng, Jie; Zhan, Renjie; Liu, Xuemei; Zuo, Hua; Huang, Cheng Zhi; Mao, Chengde
Abstract: Reconfigurable molecular events are key to molecular machines. In response to external cues, molecular machines rearrange/change their structures to perform certain functions. Such machines exist in nature, for example cell surface receptors, and have been artificially engineered. To be able to build sophisticated and efficient molecular machines for an increasing range of applications, constant efforts have been devoted to developing new mechanisms of controllable structural reconfiguration. Herein, we report a general design principle for pH‐responsive DNA motifs for general DNA sequences (not limited to triplex or i‐motif forming sequences). We have thoroughly characterized such DNA motifs by polyacrylamide gel electrophoresis (PAGE) and fluorescence spectroscopy and demonstrated their applications in dynamic DNA nanotechnology. We expect that it will greatly facilitate the development of DNA nanomachines, biosensing/bioimaging, drug delivery, etc. Abstract : DNA movement : The rational design of pH‐responsive DNA motifs is reported. The developed design principles are not limited to certain motifs and can be applied for general DNA sequences. The designed DNA motifs are analyzed by polyacrylamide gel electrophoresis (PAGE) and fluorescence spectroscopy to demonstrate their potential for applications in dynamic DNA nanotechnology.